Respostas

2014-05-22T16:23:28-03:00
A)x²-3x-10 = 0
D=(-3²)-4.1.(-10)
D=9+40
D=49
x'=3+7/2.1
x'=10/2
x'=5
x"=3-7/2.1
x"=-4/2
x"=-2

b) 6x²-x-1 = 0
D=(-1²)-4.6.(-1)
D=1+24
D=25
x'=1+5/2.6
x'=6/12
x'=3/6
x"=1-5/2.6
x"=-4/12
x"=-2/6

c)2x²-6x-140 = 0
D=(-6²)-4.2.(-140)
D=36+1120
D=1156
x'=6+34/2.2
x'=40/4
x'=4
x"=6-34/2.2
x"=-28/4
x"=-7

d)x²+9x+8 = 0
D=9²-4.1.8
D=81-32
D=49
x'=-9+7/2.1
x'=-2/2
x'=-1
x"=-9-7/2.1
x"=-16/2
x"=-8

e)x²-6x+8 = 0
D=(-6²)-4.1.8
D=36-32
D=4
x'=6+2/2.1
x'=8/2
x'=4
x"=6-2/2.1
x"=4/2
x"=2

f)3x²-x-2= 0
D=(-1²)-4.3.(-2)
D=1+24
D=25
x'=1+5/2.3
x'=6/6
x'=1
x"=1-5/2.3
x"=-4/6
x"=-2/3

g) x²-x+6= 0
D=(-1²)-4.1.6
D=1-24
D=-23 Não temos raizes reais porque o delta é negativo

h)(x+3).(x+2)-2x=16
x²+2x+3x+6-2x=16
x²+3x-10=0
D=3²-4.1.(-10)
D=9+40
D=49
x'=-3+7/2.1
x'=4/2
x'=2
x"=-3-7/2.1
x"=-10/2
x"=-5
1 5 1
Fiz rápido aqui, da uma conferida pra ver se esta tudo certo
Okay, obrigada.